(untitled) (Proceedings of the World Conference on Waste Management, 2021)
A circular economy (CE) model provides an opportunity for the construction industry (CI) to keep the end-of-life materials in a closed loop with their maximum value while advocating the reduction of significant waste generation and natural resource extraction for the built environment. While previous studies in different geographical regions have been individually carried out on investigating the government engagement in the CE, no solitary study exists that holistically focus upon the role of government that steers the CI towards a CE. With this concern, the objectives of the current study are twofold. First, to investigate the roles through which the government contributes to implementing CE in the CI. Second, it outlines the potential research directions for future researchers to expand the domain under study. To achieve these objectives, a systematic literature review (SLR) was conducted based on the review protocol, Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). A total of 125 articles available in four search engines from 2002 to 2020 were incorporated for both descriptive and content analysis. Most articles (19) were published in the year 2019, and China is the dominant country for publishing most of the articles in the area under study. The study found that the government influences the CE in the CI by playing four significant roles: regulating, subsidizing, encouraging and informing. Herein, the government should play these four roles jointly with the amalgamation of government agencies, research institutions and nongovernment associations. The article concludes by outlining the future research priorities to advance the understanding in the domain under study. The value of the study is that it explores an overlooked area in the existing literature while providing a direction for the CI practitioners to understand the government role in paving the path to a CE.